Pulmonary solid adenocarcinoma in a dog. (February 2023) - Michishita, Masaki; Hanari, Naoki; Oda, Hitomi; Nagashima, Tomokazu; Machida, Yukino; Hamamoto, Yuji; Tamura, Kyoichi; Azakami, Daigo; Ochiai, Kazuhiko; Mori, Akihiro
Abstract: A 12-year-old castrated male Beagle dog presented with a 1-month history of progressive loss of appetite and cough. One month after the initial visit, a detailed clinical examination was performed due to weight loss and persistent cough. Computed tomography demonstrated diffuse opacification of the entire right lung and cranial lobe of the left lung. Samples of the pulmonary lesions obtained by fine-needle aspiration (FNA) were highly cellular with scattered and clustered foci of large round cells, suggestive of a round cell tumour. Ten days after the FNA, the dog was euthanized due to decreased activity and severe respiratory symptoms. At necropsy, enlargement of the entire right lung and cranial lobe of the left lung was seen. The external and cut surfaces of the lungs were homogeneously grey–white. Histopathological examination of sections of the right lung and the cranial lobe of the left lung revealed proliferation of large round or polygonal neoplastic cells arranged in nests of variable size separated by a thin fibrous stroma. Neoplastic cells were immunopositive for cytokeratin and thyroid transcription factor-1 but negative for vimentin, CD204, chromogranin A and synaptophysin. On the basis of these findings, the tumour was diagnosed as pulmonary solid adenocarcinoma.